Synergy Magic Chess Optimization for 3 Evolution with Binary Integer Programming (Case Study Magic Chess v.255.1) - Jovian Dian Pratama; Ratri Wulandari Wulandari; Imas Wihdah Misshuari (Journal of Games, Game Art, and Gamification, 2023)
Mobile Legends: Bang Bang or MLBB is a game with the Multiplayer Online Battle Arena or MOBA genre and this game genre is part of Action Real Time Strategy. This arcade mode game consists of brawl and magic chess. In magic chess mode, each player must arrange pawns in the form of heroes to create a strong synergy to defeat the opposing troops. In addition to synergy combos to manage playing strategies in Magic Chess, there are Line up heroes or hero ranks, to get synergy with 3 evolutions. The integer program can be used in designing a strategy for playing Magic Chess with the QM for Windows v5 application. Binary PBB. The objective function modeling minimizes the number of heroes used, the problem is the number of hero slots and synergies that players want, as well as the limiting value of the binary variables, namely when 0 heroes are not used or 1 when the hero is used, the solution obtained is the formulation to optimize Synergy with 3 Evolution.